WEED MANAGEMENT IN SOYBEAN ( YBEAN (GLYCINE MAX L.) - BALI, ARADHANA; BAZAYA, B. R; SWAMI, SANJAY (The Bioscan, 2015)
A field experiment was conducted during kharif season of 2011 at Research Farm, Sher-e-Kashmir University of Agricultural Sciences and Technology, Chatha-Jammu to evaluate the effect of integrated weed management in soybean. The highest reduction of weed population and weed dry matter was found in two hand weeding at 15 and 35 days after sowing followed by imazethapyr @ 75 g a.iha-1 (PoE) + hoeing at 35 days after sowing. Among the herbicidal treatments, highest seed yield, highest weed control efficiency (94.1%) and net return (Rs.24565.17) was observed in imazethapyr @ 75 g a.iha-1 (PoE) + hoeing at 35 days after sowing followed by quizalofop-ethyl @ 40 g a.iha-1 (PoE) + hoeing at 35 days after sowing. Application of quizalofop-ethyl @ 40 g a.iha-1 (PoE) + hoeing at 35 days after sowing recorded the highest benefit cost ratio of 1.44, which was comparable with the application of imazethapyr @ 75 g a.iha-1 (PoE) + hoeing at 35 days after sowing (1.43)